Plan Estratégico para el taller automotriz Rafael Cartuche de la ciudad de Loja - Cartuche Tamay, Johanna Mabel (2017)
This thesis aims to design a "STRATEGIC PLAN FOR THE AUTOMOTRÍZ RAFAEL CARTUCHE WORKSHOP OF THE CITY OF SHOP", considering it as a tool to efficiently organize the activities of the same with the purpose of improving the work in Team and the appropriate decision-making, to overcome the different deficiencies existing in the company, which were identified with a methodological process, where some methods and research techniques were used to extract the necessary information and establish the real situation of How is the same. The objectives were fulfilled based on the development of a situational diagnosis in which the external and internal analysis of the environment of this company is recorded. Also, with the purpose of correcting existing shortcomings, such as the lack of strategies to increase the number of clients, improve bargaining power with suppliers, lack of strategies to promote their services, and failure to train staff; Are reasons why it does not allow it to grow and to face the competition, therefore a "STRATEGIC PLAN FOR THE AUTOMOTRÍZ RAFAEL CARTUCHE WORKSHOP OF THE CITY OF SHOP" has been proposed, in such a way as to improve the existing services, to achieve A good service to citizens with quality service, always aiming to achieve customer satisfaction. The methodology that was used in the present investigation is: the inductive and deductive method, which served for the development of the investigation, as well as the techniques of direct observation to verify in real form the conditions in which the activities of The company also conducted an interview with the manager of the Automotive Workshop Rafael Cartuche, surveys of the vehicular population of the city of Loja, surveys of all the customers of the Automotive Workshop and surveys of the employees who work in the Workshop. With the analysis of all these elements described above we proceeded to the construction of the SWOT matrix, we also weighed the external and 5 internal factors, after which a high impact and weighting matrix was built that served as a technical benchmark to determine the plans Of action to be performed in this study. Within the proposal, 5 strategic objectives were delineated, the same ones that are constructed through a logical framework, in which the problem, goal, strategies, activities, policies, responsible, tactics, cost and financing are recorded. The first objective is to establish the business philosophy that includes the mission, vision, principles, values and organization chart, at a cost of $ 110.00; The second objective is the implementation of a mechanical workshop management software to strengthen the quality of the service, at a cost of $ 950.00. The third objective is to establish a training plan for the workshop staff, with A cost of $ 530.00, the fourth objective is to implement a function manual for. The automotive workshop Rafael Cartuche of the city of Loja, with a cost of $ 860.00, finally is to establish publicity plans through means of communication (Television, Radio, Written Press), with a cost of $ 1377.00; The total cost of this strategic plan is $ 3827.00 US dollars. Finally, we present the conclusions and recommendations that have been determined, after the study carried out through the strategic planning process, the same ones that will be put to the consideration of the manager of the company for its later execution.